Social value framing of physical activity in European Member State policies: a content analysis - Ritchie, I.; Nieto, I.; Brunn, M.; Mayo, X.; Jimenez, A. (Frontiers in Sports and Active Living, 2024)
Background Engagement in physical activity (PA) benefits physical and mental health as well as many other areas of society. In Europe however, 1/3 adults do not meet minimum PA recommendations. Social value, and its quantification through social return on investment (SROI) evidence, may be a useful framing to enhance PA promotion. This study aimed to assess the current use of social value framing of PA in European Union (EU) policies. Methods Content analysis of 45 EU member state policies which contain reference to PA was conducted to evaluate the presence of five social value domains and SROI evidence. Data was analysed using manual inductive coding, supported by DeepL translation and NVivo tools. Results Social value framing was present to a certain extent in existing policies, with improved health being the most commonly referenced benefit of PA, followed by reference to social and community and then environmental benefits. Acknowledgement of the positive impacts of PA on wellbeing and education was the least present. Reference to SROI evidence was also limited. Generally, policies lacked holistic recognition of the social value of PA. Policies from the health sector were particularly limited in recognising the wider benefits of PA, whilst those from the environmental sector acknowledged the widest range of co-benefits. Conclusion Adopting social value framing could be a useful approach for enhancing PA promotion. Whilst it is present to a certain extent in existing policy, this could be increased in terms of comprehensiveness to increase issue salience and multisectoral policy action.